ANALISIS PENCANTUMAN KLAUSULA BAKU DALAM PERJANJIAN SJ TRAVEL PASS DITINJAU DARI UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Dea Vania Utami; A.M. Tri Anggraini (Jurnal Hukum Adigama, 2019)
Standardized clauses have been used since the days of ancient Greece in order to ease the making of agreement. In the era of economic digital has changed many things, including the process of making an agreement. Nowadays we have assumed electronic agreement as a legal covenant. With the existence of electronic agreement, customers cannot negotiate standardized clauses on the agreement anymore. The clauses generally cause more losses rather than profit, it was caused by the traders often utilized the clauses to get more profits and deprive their responsibilities. In practice even though some regulation has become of legal protection from standardized clauses in agreements, there is still a lot agreement that have standardized clauses contradictory with the regulations. One of that agreement is Sriwijaya Air Travel Pass Agreement, which one of the clauses not suitable with the article 18 verse (1) of Law No. 8 of 1999. Which is that clauses causing some disadvantages to the customers. The standardized clause should be eliminated as it opposed with the regulations. Traders obligated to undertake the responsibility of the form of compensation to the consumers.